Towards additively manufacturing excavating tools for future robotic space exploration. Issue 8 (12th July 2020) - Hofmann, Douglas C.; Bordeenithikasem, Punnathat; Tosi, L. Phillipe; Hendry, Morgan; Yahnker, Christopher; Sunday, Cecily; Pate, Andre; Firdosy, Samad; Iten, Jeremy J.; Nuechterlein, Jacob; Stolpe, Moritz
Abstract: Multiple metal alloys, that is, Ti‐6Al‐4 V, 316 L stainless steel, MS1 maraging steel, A2 tool steel, Inconel 625 with TiC and TiB2 reinforcement, and AMZ4 bulk metallic glass, were additively manufactured through laser powder bed fusion and tested as potential excavating tools for future robotic spacecraft landing on icy planetary bodies. Mechanical specific energy as a function of blade hardness was measured for each excavating tool as it trenched through soft and hard salt, where the salt is a regolith simulant for extraterrestrial ice. A2 tool steel, MS1 maraging steel, and bulk metallic glass cutting tools were shown to perform well in the experiments. A method for using the cutting tool as a sensor was also demonstrated. Abstract : Multiple metal alloys, additively manufactured through laser powder bed fusion, were tested as potential excavating tools for future robotic spacecraft landing on icy planetary bodies. Mechanical specific energy as a function of blade hardness was measured for each excavating tool as it trenched through soft and hard salt, where the salt is a regolith simulant for extraterrestrial ice.Tool steel, maraging steel, and bulk metallic glass cutting tools were shown to perform well in the experiments and a method for using the cutting tool as a sensor was also demonstrated.